Community arts and culture initiatives in Singapore : understanding the nodal approach - Trivic, Zdravko (New York : Routledge, 2020)
"What Can Space Do for the Arts?; What Can Arts Do for Space?; and What Can Arts and Space Do for the Community? Through the lenses of creative placemaking and neighbourhood arts ecology, Trivic re-examines the position of community arts in the spatial, social and cultural landscape. Emphasising urban design considerations of complex interdependent relationships between arts, space and people, he re-explores the role of community-based arts activities in shaping urban neighbourhoods, enriching public life and empowering communities. This is divided into an analysis of spatial opportunities for the arts in the neighbourhood; and a study of the impacts of bringing arts and culture activities into local neighbourhoods and communities, using Singapore's nodal approach as a developed case study. Using spatial opportunity analysis, the book demonstrates a step-by-step procedure for identification and evaluation of the neighbourhood spaces that work best for community arts and culture activities. In the study of impacts, Trivic proposes a holistic framework for capturing and evaluating the non-economic impacts of arts and culture, on space, society, well-being, education and participation. An invaluable template for arts event organisers and artists, as well as an important reading for students and practitioners of neighbourhood planning and urban design"--
Community arts and culture: the big picture -- Impacts of arts and culture: what impacts and how to measure? -- Neighbourhood Arts and Culture Impact Assessment (NACIA) -- Spaces for the arts: what can space do for the arts? -- Activation of space through the arts: what can arts do for space? -- Arts and community: what can arts and space do for the community, and vice versa? -- Neighbourhood spatial opportunities for the arts: Singaporean heartlands -- Impacts of arts and culture: learning from Singapore -- Conclusion: supporting community arts and culture development and building creative neighbourhoods.
OCLC-licensed vendor bibliographic record.
Keywords: Community arts projects -- Singapore; Artists and community; Neighborhood planning